Calibration of pressure sensors for hand grip measurement - Wang, Y.-T.; Chen, Y.; Tsai, C.-L.; Chang, J.-H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to assess the accuracy of grip force sensors. Methods: Several standard weights were used to calibrate the grip sensor in the static condition, The descriptive statistics and linear regression were used to present the accuracy and errors. Results: Results of this study showed a high level of sensing areas linear relationship under static loading. Conclusion: Data from this study showed high accuracy of the pressure sensor. The pressure sensor could te used for hand grip measurement.